Development of a computational fluid dynamics model of an industrial scale dense medium drum separator. Issue 1 (1st January 2019) - Eggers, Arne; Peeters, Jef R.; Waignein, Luc; Noppe, Brian; Dewulf , Wim; Vanierschot, Maarten
Abstract : The European Union is setting increasingly challenging targets for the waste recycling rates of its member states. This makes improvements in recycling processes, such as dense medium metal separation, a necessity. Dense medium metal separation takes place in a dense medium drum separator where the light metal floats and can be easily separated from more heavy metal, which will sink. Although dense medium separation has been applied in the coal and mineral mining industry for decades, prior research on modeling this process only focuses on first order models using measurement data of running installations. Such an approach, however, can not be applied to optimize the design of a separator. To overcome this drawback and to obtain new insights in the optimization of dense medium drums, a computational fluid dynamics based model is presented and validated in this paper. This model estimates the influence of these non-modelled effects on the separation efficiency in real industrial applications. Based on this study general guidelines are presented. Implementation of these to a separator resulted in an efficiency increase of roughly 5%, corresponding to an extra 2800 tons of aluminum separated each year.